2019
DOI: 10.1039/c9nr06682a
|View full text |Cite
|
Sign up to set email alerts
|

All-inorganic perovskite CsPbBr3 microstructures growth via chemical vapor deposition for high-performance photodetectors

Abstract: Perovskite cesium lead halide (CsPbBr3) has attracted considerable attention due to its excellent optoelectronic properties and superior stability against moisture, oxygen, light, and heat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…Figure a shows the I–T curve for the MAPbI 3 /C8BTBT heterojunction photodetector up to 3000 s. Compared with conventional perovskite photodetectors, the device can operate continuously, stably, and without attenuation, which is very valuable for the practical application of the perovskite photodetectors. [ 19,23–25 ] In addition, compared with the MAPbI 3 photodetector in this work, the photocurrent of the MAPbI 3 /C8BTBT heterojunction photodetector is greatly improved in the “on” state. After storage at 35% humidity for 2 months, Figure 4b shows that the MAPbI 3 /C8BTBT heterojunction photodetector still operate reliably, with no attenuation visible in the I–T curve up to 3000 s. The insets in Figure 4a,b show the photocurrent of the MAPbI 3 /C8BTBT photodetector in the “on” state at 1500 s. The MAPbI 3 /C8BTBT heterojunction photodetector can maintain 93.7% of the initial current after storage at 35% humidity for 2 months.…”
Section: Figurementioning
confidence: 88%
See 1 more Smart Citation
“…Figure a shows the I–T curve for the MAPbI 3 /C8BTBT heterojunction photodetector up to 3000 s. Compared with conventional perovskite photodetectors, the device can operate continuously, stably, and without attenuation, which is very valuable for the practical application of the perovskite photodetectors. [ 19,23–25 ] In addition, compared with the MAPbI 3 photodetector in this work, the photocurrent of the MAPbI 3 /C8BTBT heterojunction photodetector is greatly improved in the “on” state. After storage at 35% humidity for 2 months, Figure 4b shows that the MAPbI 3 /C8BTBT heterojunction photodetector still operate reliably, with no attenuation visible in the I–T curve up to 3000 s. The insets in Figure 4a,b show the photocurrent of the MAPbI 3 /C8BTBT photodetector in the “on” state at 1500 s. The MAPbI 3 /C8BTBT heterojunction photodetector can maintain 93.7% of the initial current after storage at 35% humidity for 2 months.…”
Section: Figurementioning
confidence: 88%
“…The CVD method is widely used in the preparation of semiconductor materials. [ 25,26 ] Compared with the solution method, it can effectively reduce the defects in the material and improve the stability. In this work, as shown in Figure a, the MAPbI 3 film was prepared using CVD method.…”
Section: Figurementioning
confidence: 99%
“…In the literature, pioneer works have reported various structures that can be grown by CVD method. For instance, micron sized crystallites can be grown epitaxially on single crystal substrates; [ 12a,14,25 ] nanowires as well as heterostructures are also demonstrated for high performance photo‐detectors. [ 12c,29 ] In order to achieve large scale growth with well controlled nano/micron structures, the growth conditions worth in‐depth investigations.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Moreover, by tuning the deposition temperature, different micro‐structures such as microwires (380 °C), microplates (340 °C), and triangular pyramids (300 °C) can be synthesized. [ 14 ] Interestingly, recent reports also demonstrated the epitaxial growth of CsPbBr 3 on various substrates [ 12a–c ] which exhibit excellent charge transport properties for optoelectronics applications. While few studies have reported the successful growth of large size single‐crystalline CsPbBr 3 grains via CVD method and unravel their CVD growth mechanism are highly demanded and urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, CVD method with high level of controllability, versatility and scalability has been considered as a promising method for achieving high quality WGM perovskite nanocavities. Various high quality WGM perovskite nanocavities have been successfully grown on mica substrate [8,11,12]. However, the di culty in transferring WGM perovskite nanocavities to desired surfaces while maintaining the high quality limits their applications [13,14].…”
Section: Introductionmentioning
confidence: 99%